Do Well-functioning THAs Retrieved at Autopsy Exhibit Evidence of Fretting and Corrosion?. Issue 10 (October 2018) - Lange, Jeffrey; Wach, Amanda; Koch, Chelsea N.; Hopper, Robert H.; Ho, Henry; Engh, Charles A.; Wright, Timothy M.; Padgett, Douglas E.
Abstract: Background: Our understanding of fretting and corrosion at head-neck junctions in modular THAs in vivo is based largely on the analysis of retrieved implants removed for various diagnoses. Little is known about the condition of head-neck tapers in well-functioning THAs. Questions/purposes: Regarding a cohort of well-functioning autopsy-retrieved modular THAs, we asked: (1) Does trunnion geometry or femoral head material affect the pull-off force of the femoral head? (2) Is there a relationship between trunnion damage and length of implantation time, head diameter, and neck length? (3) Does visual damage scoring accurately determine the presence or absence of corrosion on cobalt-chrome trunnions? Methods: Sixty-six femoral stems and engaged femoral heads were retrieved at autopsy from 53 patients at Anderson Orthopaedic Research Institute from 1998 to 2014. Ten stems were excluded for low stem design group size or insufficient head-stem clearance for pull-off testing, leaving a cohort of 56 THAs with a median implantation time of 10 years (range, 1-24 years). The femoral stems included three cobalt-chrome (CoCr) designs from a single manufacturer with either a 12/14 or 14/16 trunnion design (N = 36 and 20, respectively) mated with alumina or CoCr heads (N = 13 and 43, respectively). The force required to pull off the femoral heads was measured using a uniaxial load frame according to ASTM F2009-00. Mating surfaces were visually examined to assess the presence and severity of fretting and corrosion using a modified Goldberg scoring system. Three 12/14 trunnions of similar implantation lengths and varied damage scores were selected for imaging with a scanning electron microscope (SEM) and energy dispersive x-ray analysis (EDAX) to confirm the absence or presence of corrosion damage. Results: No difference was seen in pull-off force between groups based on trunnion geometry and head material (median [range], alumina-12/14: 3127 [2320-6992] N, alumina-14/16: 2670 [1095-7919] N, CoCr-12/14: 2255 [1332-5939] N, CoCr-14/16: 2812 [1655-4246] N; p = 0.132). A positive correlation was found between damage score and length of implantation (ρ = 0.543, p < 0.001). However, no correlation between damage score and either head diameter or neck length was found (ρ = -0.012, p = 0.930 and ρ < 0.001, p = 0.995, respectively). In all, 39 of 56 specimens demonstrated no fretting or corrosion, and 16 specimens had mild damage scores. One specimen demonstrated severe corrosion without visual evidence of fretting. The presence of intergranular corrosion on this trunnion was determined by SEM imaging and EDAX. The absence of corrosion products on two trunnions with no observed damage was confirmed. Conclusions: This study found little evidence of fretting and corrosion in a cohort of well-functioning CoCr-CoCr and alumina-CoCr head-neck couples. Further studies are necessary to characterize fretting and corrosion at head-neck junctions of well-functioning implants of other designs and manufacturers. Clinical Relevance: The results from this study suggest that patients with well-functioning THAs using polyethylene bearing surfaces with alumina or CoCr heads appear to be at low risk for trunnion corrosion for the specific CoCr alloy stems and trunnion geometries analyzed here.